Design Of A Debit And Credit Financial Information System Prototype Method - Ami Abdul Jabar; Zulham Sitorus; Sipra Barutu; Nelviony Parhusip (SEAN Institute, 2023)
The absence of an available financial information system makes it difficult to record financial records and prepare financial reports, making it difficult for company leaders to understand their company's financial condition and make decisions. The legal entity company which was founded in 2018 has not yet utilized technology in carrying out financial records and preparing financial reports, especially debits and credits. This research aims to design a debit and credit Financial Information System using the Prototype Method at PT Bangkit Mulya Prakoso Teknik.The results include relational database design, activity diagrams, use case diagrams, and interface displays. It is hoped that this system design can improve corporate financial governance, make a significant contribution, and become a role model for other companies facing similar challenges.